Analisis Faktor Lingkungan Terhadap Tumbuh Kembang Anak Usia Dini - Indah Khairani; Miftahul Jannah; Siti Nurhaliza; Khadijah Khadijah; Homsani Nasution (Mathematics Education Study Program, 2025)
This study aims to analyze environmental factors that influence the development of early childhood based on parents’ perspectives. The research employs a qualitative approach using in-depth interviews with three parents of young children residing in Jl. Tembung Pasar 2, Percut Sei Tuan District, Deli Serdang Regency. The data were analyzed using thematic analysis to identify key themes derived from the participants’ experiences and viewpoints. The findings indicate that a supportive family environment, stimulating activities at home, social interactions with peers, adequate educational facilities, and positive adult role models significantly contribute to children’s development. This study highlights that early childhood development is not solely determined by biological factors, but also strongly shaped by the quality of the surrounding social, emotional, and physical environment. These findings are expected to serve as a reference for parents, educators, and policymakers in creating environments that are more conducive to early childhood development.